Prevention of Risky Sexual Behaviour through the Formation of Psychological Readiness to Parenthood - Krysko A.A., (Психолого-педагогические исследования, 2018)
In the world there are tendencies of early entering into sexual relations and simultaneous withdrawal of the age of marriage, an increase in the number of early pregnancies and abortions among minors. Existing programs for the prevention of risky sexual behavior are ineffective, since they are one-time, narrowly focused. The author presents the results of an experiment on the prevention of risky sexual behavior in adolescents based on the formation of their ideas of parenting and child-parent relations, and through the prism of this topic, allowing to build an image of reproductive behavior in the present and future. The program is designed taking into account the psychology of modern adolescents, in accordance with the principles of awareness and responsibility, is based on a restorative approach and resource approach to the formation of psychological readiness for parenthood M.E. Lantsburg. The program for the development of psychological preparedness for parenting in adolescents has two targets: the nearest: preventing adolescent pregnancy and reducing its negative consequences in the event of an early pregnancy, and strategic - preparing for the planning and birth of the coveted child in the future. The results prove that the adolescents' views about the family depend both on the experiences they experienced in their own childhood and on the trends in the social and political space discussed in this topic. The study showed that adolescents' views on sexual relations, family and parenthood can be purposefully influenced through a program based on the knowledge of age-related psychology, resource and recovery approaches and using interactive methods of teaching relevant to this age group.